2014
DOI: 10.1111/tmi.12339
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: Hygiene and health: systematic review of handwashing practices worldwide and update of health effects

Abstract: Abstractobjective To estimate the global prevalence of handwashing with soap and derive a pooled estimate of the effect of hygiene on diarrhoeal diseases, based on a systematic search of the literature.methods Studies with data on observed rates of handwashing with soap published between 1990 and August 2013 were identified from a systematic search of PubMed, Embase and ISI Web of Knowledge. A separate search was conducted for studies on the effect of hygiene on diarrhoeal disease that included randomised cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
386
3
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 409 publications
(411 citation statements)
references
References 47 publications
10
386
3
12
Order By: Relevance
“…However, there is concern that both adult and child participants provided responses which they perceived the researchers wanted or expected to hear. This courtesy bias has been shown to occur in other hygiene interventions (Freeman et al, 2014). For example, practically all children said they washed their hands with soap after using the latrine, before and after the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is concern that both adult and child participants provided responses which they perceived the researchers wanted or expected to hear. This courtesy bias has been shown to occur in other hygiene interventions (Freeman et al, 2014). For example, practically all children said they washed their hands with soap after using the latrine, before and after the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Family support is one of the factors that influence an individual's behaviors in taking right decisions. The presence of family support might encourage behavioral capacity and willingness (Freeman et al, 2014). High self-efficacy might cause an individual to endure longer in more difficult problems, to throw away ineffective problem solving activities, to be quicker in selecting strategies, to review any mistakes in their work, to prepare themselves toward more challengeing objectives to spend lesser time in being anxious toward the consequences of failure (WSP, 2008).…”
Section: The Influence Of Perceived Barriersmentioning
confidence: 99%
“…Bariers in performing disease-preventing behaviors include: cost, culture and difficulty in providing facilities (sufficient facilities and clean water are not available) (Asamani, 2011;Freeman et al, 2014). The awareness toward barriers that might appear needs anticipation and needs to be calculated within the healthy behaviors of an individual both as prevention and as preliminary handling of the health problems that he or she has.…”
Section: The Influence Of Perceived Barriersmentioning
confidence: 99%
“…In a recent systematic review, it was observed handwashing with soap in 19 countries, that only 19% of people worldwide wash their hands after potential contact with excreta. [9] Consequence of IDA Among Pregnant Women IDA early in pregnancy may increase the risk of having a premature delivery or a low birth weight baby. [10] When maternal iron stores are depleted, the fetus also cannot accumulate much iron resulting in decrease in fetal iron stores.…”
Section: Introductionmentioning
confidence: 99%